An evaluation of Lean deployment in Irish micro-enterprises. (19th May 2023) - Nelson, Stuart; McDermott, Olivia; Woods, Bobby; Trubetskaya, Anna
Abstract : This study investigates the reasons for Lean deployment in Micro Enterprises, the types of tools used, the challenges involved and the results obtained in Micro Enterprises in Ireland. Qualitative interviews were conducted with 22 Micro Enterprises in Ireland that have started Lean implementation over the last three years. Lean offers many benefits to Micro Enterprises similar to those observed in larger-sized enterprises, including improved productivity, quality and reduced costs. In addition, leadership support for Lean in Micro Enterprises is not a challenge for Lean deployment as many Micro Enterprises are owner-managers and thus embrace and facilitate the deployment of Lean in organisations. Furthermore, a Critical success factor for Lean in Micro Enterprises is government support and availability of Lean mentorship. Further longitudinal studies on Micro Enterprises would help study how Lean evolves in these organisations over time especially in enterprises who have employed Lean for several Leans. This is one of the first studies specific to the practical application of Lean in ME's in Ireland and globally. For academics and practitioners and informing government funding policy, this study demonstrates that Lean can successfully be deployed in Micro Enterprises. This study demonstrates that government supports can aid Lean and enhance economic competitiveness.